A Freire based action-research approach to learning Italian as foreign language by migrant adults - Alessio Surian; Consuelo Surian (LESLLA Symposium Proceedings, 2021)
Summary coming from the work itself: "The paper presents the work of an action-research group that aims at connecting Paulo Freire’s adult education approach to learning Italian as foreign language by migrants in the Veneto region. It offers a brief description of this literacy approach followed by a critical analysis of some of the key issues in adapting it to illiterate migrants focusing on generative (key) words and how to use them within the learning process. Examples are provided on how to identify and to play with syllables in order to create cluster families and to generate new words and sentences. Further information is provided on the first year (2018-19) of actionresearch work involving teachers of Italian as foreign language in different contexts around Padova where the project is co-ordinated by the CPIA adult education centre. The common focus and reflective practice is centred on structuring learning units that make use of playful and participatory activities and that follow the gestalt approach, i.e. going through four steps, including motivation, global approach, analysis, synthesis and reflection."
Keywords: Generative word; Non-literate migrants; Adult learning; Action-research